2017
DOI: 10.3390/en10122112
|View full text |Cite
|
Sign up to set email alerts
|

Bioethanol Production from Cachaza as Hydrogen Feedstock: Effect of Ammonium Sulfate during Fermentation

Abstract: Abstract:Cachaza is a type of non-centrifugal sugarcane press-mud that, if it is not employed efficiently, generates water pollution, soil eutrophication, and the spread of possible pathogens. This biomass can be fermented to produce bioethanol. Our intention is to obtain bioethanol that can be catalytically reformed to produce hydrogen (H 2 ) for further use in fuel cells for electricity production. However, some impurities could negatively affect the catalyst performance during the bioethanol reforming proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 55 publications
2
5
0
Order By: Relevance
“…In 2017, 2718 t of oil equivalents (toe) of bioethanol was consumed for transport in Europe, of which 121 toe was consumed by the Netherlands [33]. Although much research has been done on the ethanol production from lignocellulosic biomass [34][35][36][37][38][39][40][41][42][43][44], the economic viability of a bioethanol plant in the Northern Netherlands is yet unknown. Therefore, this research aims to investigate the feasibility of a bioethanol plant treating organic residues (sugar beet pulp and grass straw) in the Northern Netherlands.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, 2718 t of oil equivalents (toe) of bioethanol was consumed for transport in Europe, of which 121 toe was consumed by the Netherlands [33]. Although much research has been done on the ethanol production from lignocellulosic biomass [34][35][36][37][38][39][40][41][42][43][44], the economic viability of a bioethanol plant in the Northern Netherlands is yet unknown. Therefore, this research aims to investigate the feasibility of a bioethanol plant treating organic residues (sugar beet pulp and grass straw) in the Northern Netherlands.…”
Section: Introductionmentioning
confidence: 99%
“…Afterward, came clarification at which point the juice was purified, with all impurities removed in the form of insoluble calcium salts (Consorcio 2012 ). Sucrose was then recovered from these solid impurities by filtration, to obtain juice and a solid by-product (sugarcane press mud) which can be used as compost (Consorcio 2012 ; Sanchez et al 2017 ).…”
Section: Block Ii: Raw Materials Processing Stagementioning
confidence: 99%
“…Samples were fermented in 15 mL centrifuge tubes with a total volume of 4 mL and an inoculum size of 10 vol.%. Inoculum was prepared according to previous studies [14]. Dry Saccharomyces cerevisiae (Ethanol Red ® , Fermentis by Lesaffre, Marcq-en-Baroeul, France) was activated in water at 30 • C for 20 min.…”
Section: Fermentationmentioning
confidence: 99%
“…Their formation is influenced by different variables such as nitrogen, temperature, pH, dissolved oxygen, and yeast strain [12,13]. For instance, we reported that the addition of ammonium sulfate ((NH 4 ) 2 SO 4 ) decreased the amount of fusel alcohol, mainly 2-methyl-1-propanol, during the fermentation of sugarcane press-mud at 30 • C [14]. Arshad et al [15] assessed the effect of several fermentation variables, such as substrate concentration, pH, and inoculum size, over the fusel alcohol concentration during fermentation of sugarcane molasses at 30 • C. They concluded that all the assessed variables have a significant effect (p < 0.05) over the formation of fusel alcohols.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation